Caliban and the Yankees : Trinidad and the United States occupation - Neptune, Harvey R., 1970- (Chapel Hill : University of North Carolina Press, 2007)
In a compelling story of the installation and operation of U.S. bases in the Caribbean colony of Trinidad during World War II, Harvey Neptune examines how the people of this British island contended with the colossal force of American empire-building at a critical time in the island's history. The U.S. military occupation between 1941 and 1947 came at the same time that Trinidadian nationalist politics sought to project an image of a distinct, independent, and particularly un-British cultural landscape. The American intervention, Neptune shows, contributed to a tempestuous scen.
The turbulent thirties: shaking empire, making nation -- The American preoccupation: assessing the United States before the war -- Laboring over the Yankee dollar: work in occupied Trinidad -- From barefooted men to saga boys: gender, class, and clothes in occupied Trinidad -- Yankees in the land of the calypso: promoting and patronizing Trinidadian nationality -- Love American style: race, gender, and sexuality in occupied Trinidad -- Coda. Re-membering Caliban and the Yankees: the politics of history.
Includes bibliographical references (pages 247-268) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Nationalism -- Trinidad and Tobago -- History -- 20th century; Trinidad and Tobago -- Civilization -- American influences; Trinidad and Tobago -- History -- 20th century; Nationalisme -- Trinité-et-Tobago -- Histoire -- 20e siècle.; Trinité-et-Tobago -- Histoire -- 20e siècle.; HISTORY -- Caribbean & West Indies -- General; Civilization -- American influences; Nationalism; Trinidad and Tobago; 15.85 history of America; Occupations; Americans; Trinidad and Tobago; United States of America; Trinidad and Tobago; Nationalism; Foreign armed forces; World War II; Culture; History; 1900-1999; 1940-1950; History